THE INTERNAL AND EXTERNAL FACTORS CAUSE SPEAKING ANXIETY ON STUDENTS’ AT SECOND SEMESTER OF ENGLISHEDUCATION DEPARTMENT IN GIVING PRESENTATION - Wawat Srinawati; Andika Maulana (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
Intro The purpose of this study is to investigate speaking anxiety of English Education Department students in STKIP Muhammadiyah Bogor during presentation. The subject of the study are students in English Department student’s at second semester, The took subject 26 students in class A at second semester. The writer try to identify what are the internal and external factors that may contribute to anxiety in English learning especially when giving presentation and. This research used descriptive qualitative method. The result of this showed From the data analysis result in questionnaire, the writer found that the most of students are at “Medium anxiety” level without “Relaxed” and Very Relaxed. There are 6 (23%) students who experience “High Anxiety” level, 11 (42%) students are in “Medium Anxiety” level, and 9 (35%) students from 26 students, is in “Low Anxiety” Level. The result of this research show that from psychological aspect almost a half of students (42%) are in the level of moderate anxiety, 6 students (23%) are in the level of severe anxiety, and9 students (35%) are in the level mild anxiety. The source of anxiety are not only from internal factor but also from external factor, those factors are: afraid of classmate, and the role of lecturers.